2023
DOI: 10.3389/fpsyg.2023.1165911
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of quality of life due to COVID-19-induced long-term olfactory dysfunction

Abstract: IntroductionOlfactory dysfunction is one of many long-lasting symptoms associated with COVID-19, estimated to affect approximately 60% of individuals and often lasting several months after infection. The associated daily life problems can cause a decreased quality of life.MethodsHere, we assessed the association between perceived quality of life and both qualitative and quantitative olfactory function (distorted and weakened sense of smell, respectively) in 58 individuals who had undergone confirmed SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…The signi cative difference between NG and ODG at 6 months on the quality of life and hedonic experience was consistent with data from the literature (40,41). For example, an online survey of 322 COVID-19 positive subjects who had experienced a loss of smell or taste, reported 87% reduced enjoyment of food, 56% decreased enjoyment of life in general, and 55% loss of appetite (18).…”
Section: Discussionsupporting
confidence: 79%
“…The signi cative difference between NG and ODG at 6 months on the quality of life and hedonic experience was consistent with data from the literature (40,41). For example, an online survey of 322 COVID-19 positive subjects who had experienced a loss of smell or taste, reported 87% reduced enjoyment of food, 56% decreased enjoyment of life in general, and 55% loss of appetite (18).…”
Section: Discussionsupporting
confidence: 79%
“…Clusters 1 and 4, which had significantly poorer QOL scores at 3 months compared with other clusters, improved over time but were still significantly poorer than cluster 2 at 6 and 12 months. The presence of long COVID symptoms has been reported to be associated with lower QOL, 43 44 and the improvement in QOL over time may be due to a decrease in symptoms after the illness, but clusters 1 and 4, where symptoms remained even at 6 and 12 months, did not recover to the extent of cluster 2. In cluster 5, EQ-5D-5L Visual Analogue Scale and SF-8 MCS were worse at 12 months than at 6 months, a different trend from that of the other clusters.…”
Section: Discussionmentioning
confidence: 96%
“…The QOL scores were similar to those of cluster 2. Some reports have suggested that taste and smell disorders are associated with lower QOL 43 44 ; however, they could be milder than neuropsychiatric and respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in terms of QOL, Miwa et al (2001) found that patients with a perceived resolution of olfactory compromise have a higher QOL than those with continuing olfactory impairment. Similarly, Brämerson, Merkonidis et al (2015), Winter et al (2023), and Gary et al (2023) asserted that anosmia negatively affects the QOL of patients. These results are supported by other studies (Elkholi, Abdelwahab, & Abdelhafeez, 2021;Bakhsh et al, 2023;Mattos et al, 2023).…”
Section: Discussionmentioning
confidence: 97%